Popular Culture - Noah Berlatsky
Each anthology in the new Global Viewpoints series (which does not duplicate any material in the Opposing Viewpoints series) delivers contemporary perspectives on the featured issue -- with the majority of the material reflecting stances of countries other than the United States. Primary sources, including speeches and government documents, join essays from international magazines and news sources for a truly panoramic view. Helpful features include an annotated table of contents, a world map and country index, a bibliography and a subject index.